2001
DOI: 10.1175/1520-0477(2001)082<2217:btbobm>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

BOBMEX: The Bay of Bengal Monsoon Experiment

Abstract: The first observational experiment under the Indian Climate Research Programme, called the Bay of Bengal Monsoon Experiment (BOBMEX), was carried out during July-August 1999. BOBMEX was aimed at measurements of important variables of the atmosphere, ocean, and their interface to gain deeper insight into some of the processes that govern the variability of organized convection over the bay. Simultaneous time series observations were carried out in the northern and southern Bay of Bengal from ships and moored bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
157
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 207 publications
(172 citation statements)
references
References 35 publications
14
157
1
Order By: Relevance
“…Over the Bay of Bengal and the north and northeast India, Class I clouds dominate other cloud types, thus indicating that the overshooting convection over these areas is very likely possible. The Bay of Bengal is, in fact, considered as an important region where convection is often very deep and intense during monsoon (Bhat et al, 2001;Zuidema, 2003).…”
Section: Spatio-temporal Distribution Of Hoicsmentioning
confidence: 99%
“…Over the Bay of Bengal and the north and northeast India, Class I clouds dominate other cloud types, thus indicating that the overshooting convection over these areas is very likely possible. The Bay of Bengal is, in fact, considered as an important region where convection is often very deep and intense during monsoon (Bhat et al, 2001;Zuidema, 2003).…”
Section: Spatio-temporal Distribution Of Hoicsmentioning
confidence: 99%
“…(c) Same as (b), but for rainfall and divergence (Unit: 10 À6 s À1 ). Shaded areas: >4 mm day À1 (IIOE) in the mid-1960s and in 1975-1976, the FGGE Monsoon Experiments in 1978-1979 (MONEX) (Krishnamurti 1985), the Coupled Ocean-Atmosphere Response Experiment in 1992-1993 (TOGA-COARE) (Webster and Lukas 1992), the GEWEX Asian Monsoon Experiment (GAME) in 1996-2000 (GAME ISP, 1998), the South China Sea Monsoon Experiment (SCSMEX) in 1996-2000 (Lau et al 2000;Ding and Liu 2001;Johnson et al 2004), the Bay of Bengal Monsoon Experiment (BO-MEX) in 1999 (Bhat et al 2001) and the Joint Air-Sea Monsoon Interactive Experiment (JAS-MINE) in 1999 and the Arabian Sea Monsoon Experiment (ARMEX) in 2002 (Webster et al 2002). At the same time, a number of books, monographs and review papers written in English summarizing the major scientific achievements of the Asian monsoon in different periods have been published, including Monsoon Meteorology (Ramage 1971), Southwest Monsoon (Rao 1976), Monsoons (Fein and Stephens 1987), Monsoon Meteorology (Chang and Krishnamurti 1987), Monsoon over China (Ding 1994), The East Asian Monsoon (Chang 2004), The Global Monsoon System (Chang et al 2005) and The Asian Monsoon .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we particularly focus on extended monsoon -breaks, which are longer than 2 weeks. It is well recognized that air-sea exchanges on intraseasonal timescales in the tropical Indian Ocean give rise to significant fluctuations of sea surface temperature (SST) and heat fluxes at the ocean-atmosphere interface (Rao, 1987;Krishnamurti et al, 1988;Bhat et al, 2001;Sengupta and Ravichandran, 2001;Veechi and Harrison, 2002). Earlier studies have reported anomalous warming of SST preceding a convection maximum in association with positive shortwave and latent heat flux anomalies into the surface (e.g.…”
Section: Introductionmentioning
confidence: 99%